Cobalamin (Vitamin B12) Induced a Shift in Microbial Composition and Metabolic Activity in an in vitro Colon Simulation - Xu, Yuanyuan; Xiang, Shasha; Ye, Kun; Zheng, Yiqing; Feng, Xiao; Zhu, Xuan; Chen, Jie; Chen, Yuewen (Frontiers in Microbiology, 2018)
Cobalamin deficiency is believed to be related to disturbances in cell division, neuropathy, nervous system disease and pernicious anaemia. Elderly people are usually advised to supplement their diets with cobalamin. As cobalamin has several forms, the effects of different forms of cobalamin on gut microbiota were investigated in this study. After seven days of supplementation, methylcobalamin had reduced the diversity of gut microbiota compared to that in the control and cyanocobalamin groups. After supplementation with methylcobalamin, the percentage of Acinetobacter spp. had increased to 45.54%, while the percentages of Bacteroides spp., Enterobacteriaceae spp. and Ruminococcaceae spp. had declined to 11.15%, 9.34%, and 2.69%, respectively. However, cyanocobalamin had different influences on these bacteria. Both cobalamins increased the amount of short-chain fatty acids, particularly butyrate and propionic acid. The cyanocobalamin group showed increased activity of cellulase compared with that in the other two groups. According to CCA and PICRUSt analysis, methylcobalamin had a positive correlation with Pseudomonas bacteria, propionic acid, and butyrate. Methylcobalamin promoted lipid, terpenoid, and polyketide metabolism by gut bacteria, promoted the degradation of exogenous substances, and inhibited the synthesis of transcription factors and secondary metabolites. Our results indicate that the various forms of cobalamin in the food industry should be monitored and regulated, because the two types of cobalamin had different effects on the gut microbiome and on microbial metabolism, although they have equal bio-activity in humans. Given the effects of methylcobalamin on gut microbiota and microbial metabolism, methylcobalamin supplementation should be suggested as the first option.